PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Silalahi, Octavia Elisabeth; Siregar, Liper; Tarigan, Parman; Manurung, Sepbeariska (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
Purpose of this research is to discribe of receivable turnover, inventory turnover and profitability and the influence of receivable turnover and inventory turnover on the profitability at Sub Sector Food and Beverage Companies listed in the Indonesia Stock Exchange. The research design used library research. The analysis data technique such as: assumption classic test, qualitative and quantitative descriptive analysisThe regression is Ŷ = 0,019 - 0,002 X1 + 0,014 X2.Correlation coefficient is 0,874 and RSquare value is 0,764. The research hypothesis is rejected, means that receivable turnover and inventory turnover have a significant effect on profitability in Sub Sector of Food and Beverage Company simultaneously. And partially for receivable turnover H0 is accepted, means that receivable turnover has effect but insignificant on profitability, for inventory turnover H0 is rejected, it means that inventory turnover has a significant effect on profitability at Sub Sector Food and Beverage Companies listed in the Indonesia Stock Exchange.           The research suggest, company should improve sales and management should pay more attention to receivable turnover and inventory turnover as one way to improve the profitability of the company. For further researchers to expand the discussion of various other factors that influence profitability.                                                                                                Keywords: Receivable Turn Over, Inventory Turn Over and Profitability.